2018
DOI: 10.1016/j.cattod.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Ethene oligomerization on nickel microporous and mesoporous-supported catalysts: Investigation of the active sites

Abstract: Complete body of DFT-MD results, results of Monte Carlo simulations, setup and results of microkinetic modeling, additional experimental details and results (PDF) CatMAP files (ZIP) ■ AUTHOR INFORMATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 127 publications
5
92
0
Order By: Relevance
“…Focusing on the nickel-carbonyl region of interest, the most intense IR bands are clearly those peaking at 2214 and 2205 cm -1 of CO adsorbed on isolated Ni 2+ ions counterbalancing the negative charge of the zeolite framework (i.e. at ion exchange positions) 33,[42][43][44] , that is, the nickel species generally considered as the active sites in Ni-aluminosilicate catalysts 2,13,15,19,25,26 . The different CO vibration frequency for these two ion-exchanged Ni 2+ cations signs for a distinct electron accepting capability (i.e.…”
Section: Results and Discussion Elucidation Of The Active Nickel Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on the nickel-carbonyl region of interest, the most intense IR bands are clearly those peaking at 2214 and 2205 cm -1 of CO adsorbed on isolated Ni 2+ ions counterbalancing the negative charge of the zeolite framework (i.e. at ion exchange positions) 33,[42][43][44] , that is, the nickel species generally considered as the active sites in Ni-aluminosilicate catalysts 2,13,15,19,25,26 . The different CO vibration frequency for these two ion-exchanged Ni 2+ cations signs for a distinct electron accepting capability (i.e.…”
Section: Results and Discussion Elucidation Of The Active Nickel Sitementioning
confidence: 99%
“…In this regard, dual-functional materials comprised of nickel ions dispersed on acidic porous aluminosilicates such as mesoporous amorphous silica-alumina [10][11][12][13][14] , Al-doped ordered mesoporous silicas (e.g. Al-MCM-41, Al-SBA-15, and related materials) [15][16][17][18][19][20] , and zeolites [21][22][23][24][25] are the most prospective solid catalysts so far investigated for this reaction. However, catalysts based on Ni dispersed on purely microporous zeolites such as X 21 , Y 22 , and MCM-22 23 typically experience a fast deactivation due to the accumulation of heavy oligomers within the channels and cages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Nevertheless, there is accumulating evidence provided by us and others that the reaction follows the Cossee–Arlman mechanism (Scheme 1) 811 known from homogeneous catalysis. The three-dimensional structure of the Ni-aluminosilicates plays a central role in alkene oligomerization: experimental results show that dimer formation is first order in alkene pressure on Ni-silicaalumina 10,12 but second order in Ni-zeolites. 12,13 1-Butene formation is also second order in mesoporous Ni-silicaalumina at low temperatures, where it was demonstrated that condensation of ethene in the pores stabilized catalytic activity.…”
mentioning
confidence: 99%
“…Interaction of light alkenes with metal clusters has been widely studied in the past due to its important applications in the fields of fine chemistry and petroleum refining. As the smallest alkene and one of the most common probe molecules, the adsorption of ethylene on supported metal catalysts has been widely investigated [1,2,3,4,5]. Keppeler et al [3] studied ethylene hydrogenation on the NaY and KL zeolite-supported Pt 13 cluster and found ethane was the only product.…”
Section: Introductionmentioning
confidence: 99%